Social attention with real versus reel stimuli: toward an empirical approach to concerns about ecological validity - Risko, Evan F.; Laidlaw, Kaitlin E.; Freeth, Megan; Foulsham, Tom; Kingstone, Alan (Frontiers in Human Neuroscience, 2012)
Cognitive neuroscientists often study social cognition by using simple but socially relevant stimuli, such as schematic faces or images of other people. Whilst this research is valuable, important aspects of genuine social encounters are absent from these studies, a fact that has recently drawn criticism. In the present review we argue for an empirical approach to the determination of the equivalence of different social stimuli. This approach involves the systematic comparison of different types of social stimuli ranging in their approximation to a real social interaction. In garnering support for this cognitive ethological approach, we focus on recent research in social attention that has involved stimuli ranging from simple schematic faces to real social interactions. We highlight both meaningful similarities and differences in various social attentional phenomena across these different types of social stimuli thus validating the utility of the research initiative. Furthermore, we argue that exploring these similarities and differences will provide new insights into social cognition and social neuroscience.